Crop Succession and Nitrogen Splitting Fertilization in Common Bean in Newly Implemented No-tillage System - Jardim, Celso Antônio [UNESP]; Mingotte, Fábio Luiz Checchio [UNESP]; Coelho, Anderson Prates [UNESP]; Lemos, Leandro Borges [UNESP] (Springer Nature, 2023)
The management practices impact on a crop succession system in newly implemented no-tillage area should be investigated to provide more accurate recommendations. A two-year experiment (2008/2009 and 2009/2010) was conducted in Southeastern Brazil to evaluate the interactions between crop succession (grasses/legume) and nitrogen splitting fertilization in common bean in a production system with newly implemented no-tillage. The experiment was conducted in a randomized block design, in a split-plot scheme. The cropping systems (plots) in spring/summer were: sole maize, maize intercropped with Urochloa ruziziensis and sole U. ruziziensis. The subplots consisted of ten splitting schemes of side-dressing nitrogen fertilization in common bean, with applications in the phenological stages V3 (first fully expanded trifoliate leaf), V4 (third fully expanded trifoliate leaf) and R5 (opening of floral buds). On average, stages V3, V4 and R5 occurred at 12, 22 and 38 days after emergence. The common bean grain yield (GY) was 5 to 12% lower when it was cultivated after sole U. ruziziensis compared to other successions. However, when U. ruziziensis was intercropped with maize, the GY of common bean was similar to that obtained in the succession with sole maize. Compared to the application in a single rate, the GY of common bean was on average 12% higher when nitrogen fertilization was split, and the best schemes were 45-00-45 and 45-45-00. On average, sole maize, maize intercropped with U. ruziziensis and sole U. ruziziensis promoted soil surface cover by crop residues left by the harvest of 79, 100 and 100%, respectively. Nitrogen fertilization in common bean did not affect the GY of maize in succession. Intercropping of maize with U. ruziziensis and nitrogen splitting fertilization (45-00-45 and 45-45-00) in common bean in succession allows obtaining the ecosystem benefits promoted by the forage without affecting the cash crops yield.
Keywords: Grain yield; Intercropped maize; Phaseolus vulgaris L; Sustainability; Zea mays L